A silicone rubber composition and a disposable thin film fuse
Patent Information
- Application Number
- CN202310925945.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-26
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2043-07-26
AI Technical Summary
薄硅胶层的厚度非常薄,因此对硅胶层的阻燃和抗电弧性能提出了较高的要求,常规的阻燃和抗电弧材料,比如氢氧化铝,(1)为了达到更高的阻燃和抗电弧性能,需要加入很多的量,甚至要采用纳米级别的材料,但存在分散困难和/或导致胶料的粘度太大,不好加工,(2)对于阻燃和抗电弧性能的提升有一个限度,达到这个限度后继续增加用量对于性能的提升作用不大
1、本申请采用碳碳双键和环氧基共修饰的纳米氢氧化铝与氨基POSS进行反应,将POSS纳米结构接枝到纳米氢氧化铝的表面,获得POSS改性氢氧化铝,POSS结构既可以提高氢氧化铝在硅橡胶中的分散性,也可以与纳米氢氧化铝协同发挥阻燃和抗电弧烧蚀的作用,因此,本申请的硅橡胶的阻燃和抗电弧烧蚀的性能较好。
Smart Images

Figure BDA0004360298540000091 
Figure BDA0004360298540000101
Abstract
Description
Technical Field
[0001] This application relates to the field of thin-film fuse technology, specifically to a silicone rubber composition and a disposable thin-film fuse. Background Technology
[0002] One-time film fuses are time-delay switches used for overcurrent protection, requiring them to melt within a very short time when the current is too high. The surface of a film fuse is typically covered with a very thin silicone layer, approximately 0.1 mm thick. This thin silicone layer is required to have good flame-retardant and arc-resistant properties.
[0003] Relatively speaking, the thinner the material, the more prone it is to combustion, tracking, and arc erosion. The thickness of the thin silicone layer is very thin, so high requirements are placed on the flame retardant and arc-resistant properties of the silicone layer. Conventional flame retardant and arc-resistant materials, such as aluminum hydroxide, (1) require a large amount to achieve higher flame retardant and arc-resistant properties, and even require the use of nano-level materials. However, there are difficulties in dispersion and / or the viscosity of the adhesive is too high, making it difficult to process. (2) There is a limit to the improvement of flame retardant and arc-resistant properties. After reaching this limit, further increasing the amount will not have much effect on improving the performance. Therefore, aluminum hydroxide alone is difficult to meet the requirements of thin silicone layers as a flame retardant and arc-resistant filler. Summary of the Invention
[0004] To address the aforementioned technical problems, this application provides a silicone rubber composition and a disposable thin-film fuse.
[0005] The technical solution adopted in this application is as follows: A silicone rubber composition, by weight, comprises 100 parts of vinyl silicone rubber raw rubber, 20-90 parts of POSS-modified nano aluminum hydroxide, and an appropriate amount of crosslinking agent; The POSS-modified nano-aluminum hydroxide was prepared by reacting nano-aluminum hydroxide co-modified with carbon-carbon double bonds and epoxy groups with amino POSS at a weight ratio of 1:0.05-0.5.
[0006] Preferably, the vinyl and epoxy-modified nano-aluminum hydroxide is prepared by the following method: A carbon-carbon double-bond silane coupling agent and an epoxy-containing silane coupling agent are added together to anhydrous ethanol. Insufficient water is added to adjust the pH to 3-5 for hydrolysis and condensation. Water is then added to the required volume, and hydrolysis continues. Nano-aluminum hydroxide is added, and the reaction is stirred for 1-10 hours. The mixture is then filtered, washed, and dried to obtain the final product.
[0007] More preferably, the molar ratio of the carbon-carbon double-bond silane coupling agent to the epoxy-containing silane coupling agent is 3:1 to 1:3.
[0008] More preferably, the insufficient amount of water refers to a molar amount of water that is lower than the theoretical molar amount of water required for the complete hydrolysis and condensation of the carbon-carbon double-bond silane coupling agent and the epoxy-containing silane coupling agent, while the sufficient amount refers to a molar amount of water that exceeds the theoretical molar amount of water required for the complete hydrolysis and condensation of the carbon-carbon double-bond silane coupling agent and the epoxy-containing silane coupling agent.
[0009] More preferably, the average particle size of the nano-aluminum hydroxide is 5-50 nm.
[0010] More preferably, the weight ratio of the carbon-carbon double-bond silane coupling agent and the epoxy-containing silane coupling agent to the weight of the nano-aluminum hydroxide is 0.1-0.5:1.
[0011] Preferably, the aminoPOSS has the general formula (SiO2). 1.5 ) n R 1 x R 2 y , where R 1 For -CH2CH2CH2NH2, R 2 Selected from C1-C4 alkyl groups, n = 6, 8, 10 or 12, x + y = n, x = 1-2.
[0012] Preferably, the appropriate amount of crosslinking agent is 0.8-3 parts of peroxide vulcanizing agent.
[0013] Preferably, the appropriate amount of crosslinking agent is composed of 2-100 parts of hydrogen-containing silicone oil and 0.001-0.1 parts of Pt catalyst.
[0014] A disposable thin-film fuse is prepared from the raw silicone rubber described in any of the above embodiments.
[0015] Aluminum hydroxide is a commonly used inorganic filler in silicone rubber for resistance to tracking and arc erosion, and it also has some flame retardancy. Nano-sized aluminum hydroxide has an even stronger effect. However, nano-sized aluminum hydroxide is difficult to disperse in silicone rubber, resulting in the failure to achieve the desired flame retardant and arc-resistant properties.
[0016] Cage-type polysilsesquioxane, or POSS for short, is an organic-inorganic hybrid material with a three-dimensional structure and a size of about 1-3 nm. It can be well dispersed in silicone rubber and can also improve the flame retardant properties of silicone rubber.
[0017] This application combines the properties of nano-aluminum hydroxide and POSS. By modifying nano-aluminum hydroxide with POSS, it was found that this significantly improves the flame retardancy and arc erosion resistance of silicone rubber. Even very thin silicone rubber (approximately 0.1 mm thick) achieves a UL94-V0 flame retardancy rating, with a short self-extinguishing time. Under DC current, 50A current, and 32V voltage, no significant arc erosion or combustion occurs. Furthermore, the main chain structure of POSS is similar to that of silicone rubber, exhibiting good compatibility and improving the dispersibility and compatibility of nano-aluminum hydroxide in silicone rubber.
[0018] In summary, this application has the following beneficial effects: 1. In this application, nano-aluminum hydroxide co-modified with carbon-carbon double bonds and epoxy groups is reacted with amino POSS to graft the POSS nanostructure onto the surface of nano-aluminum hydroxide, thereby obtaining POSS-modified aluminum hydroxide. The POSS structure can not only improve the dispersibility of aluminum hydroxide in silicone rubber, but also synergistically exert flame retardant and arc erosion resistance with nano-aluminum hydroxide. Therefore, the silicone rubber of this application has good flame retardant and arc erosion resistance properties.
[0019] 2. Nano-aluminum hydroxide has carbon-carbon double bonds grafted on its surface, which can participate in the vulcanization of silicone rubber, further improving the compatibility between nano-aluminum hydroxide and silicone rubber. Nano-aluminum hydroxide is better and more stable in silicone rubber, and can better exert the synergistic performance of nano-aluminum hydroxide and POSS in the flame retardancy and arc erosion resistance of silicone rubber. Detailed Implementation
[0020] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions of this invention will be described in detail below.
[0021] Throughout this specification, unless otherwise specified, the terminology used herein should be understood as having the meaning commonly used in the art. Therefore, unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. In the event of any conflict, this specification shall prevail.
[0022] This application provides a silicone rubber composition, which, by weight, comprises 100 parts of vinyl silicone rubber raw rubber, 20-90 parts of POSS-modified nano aluminum hydroxide, and an appropriate amount of crosslinking agent; Furthermore, adding too much POSS-modified nano-aluminum hydroxide may result in uneven dispersion. Therefore, the amount of POSS-modified nano-aluminum hydroxide can be 35-70 parts, for example, 35, 40, 45, 50, 55, 60, 65, 70 parts, etc. Alternatively, the amount of POSS-modified nano-aluminum hydroxide can be 50-70 parts.
[0023] In this application, vinyl silicone rubber raw rubber refers to silicone rubber raw rubber whose polymer chain contains vinyl groups on its side chains. The average molecular weight of vinyl silicone rubber raw rubber can be above 200,000, and the vinyl content can be 0.01-0.5 wt%, or further, 0.03-0.3 wt%. The volatile matter content of vinyl silicone rubber raw rubber does not exceed 0.5 wt%. Excessive volatile matter content in vinyl silicone rubber raw rubber will lead to a decrease in flame retardancy and arc erosion resistance. In this application, the crosslinking method of vinyl silicone rubber raw rubber is not limited; it can be crosslinked and cured by peroxide vulcanization or by hydrosilylation vulcanization. Correspondingly, the crosslinking agents are a combination of peroxide, hydrogen-containing silicone oil, and Pt catalyst.
[0024] In the above, POSS-modified nano-aluminum hydroxide is prepared by reacting carbon-carbon double bond and epoxy group co-modified nano-aluminum hydroxide with amino POSS at a weight ratio of 1:0.05-0.5. The epoxy and amino groups have high reactivity, enabling relatively complete grafting of POSS onto the surface of nano-aluminum hydroxide, or even POSS coating of nano-aluminum hydroxide. For example, the weight ratio of carbon-carbon double bond and epoxy group co-modified nano-aluminum hydroxide to amino POSS can be 1:0.05, 1:0.1, 1:0.15, 1:0.2, 1:0.25, 1:0.3, 1:0.35, 1:0.4, 1:0.45, 1:0.5, etc.
[0025] In the preparation of POSS-modified nano-aluminum hydroxide, the carbon-carbon double bond and epoxy group co-modified nano-aluminum hydroxide and amino POSS can be added to an organic solvent for ultrasonic dispersion, followed by stirring and reaction, and then the organic solvent can be removed. There are no particular limitations on the organic solvent; it can be butyl acetate, ethyl acetate, acetone, tetrahydrofuran, 1,4-dioxane, methyl ethyl ketone, cyclohexanone, etc. There are also no particular limitations on the amount of organic solvent used; it can be 5, 8, 10, or 12 times the weight of the carbon-carbon double bond and epoxy group co-modified nano-aluminum hydroxide.
[0026] In a preferred embodiment of this application, vinyl and epoxy-modified nano-aluminum hydroxide is prepared by the following method: A carbon-carbon double-bond silane coupling agent and an epoxy-containing silane coupling agent are added together to anhydrous ethanol. Insufficient water is added to adjust the pH to 3-5 for hydrolysis and condensation. Water is then added to the required volume, and hydrolysis continues. Nano-aluminum hydroxide is added, and the reaction is stirred for 1-10 hours. The mixture is then filtered, washed, and dried to obtain the final product.
[0027] Using the above technical solution, the carbon-carbon double-bond silane coupling agent and the epoxy-containing silane coupling agent are first hydrolyzed and condensed in insufficient water. This allows several carbon-carbon double bonds and several epoxy groups to be grafted onto the surface of nano-aluminum hydroxide, resulting in a relatively uniform distribution and minimizing the possibility of competition between the two silane coupling agents leading to insufficient grafting of one agent onto the nano-aluminum hydroxide surface. Adding sufficient water further hydrolyzes the unhydrolyzed components of the two silane coupling agents, achieving a more complete and uniform grafting modification of the nano-aluminum hydroxide. Subsequent reaction with amino POSS further enhances the flame retardant and arc erosion resistance properties of silicone rubber.
[0028] In a more preferred embodiment of this application, the molar ratio of the carbon-carbon double-bond silane coupling agent to the epoxy-containing silane coupling agent is 3:1 to 1:3. In this application, the carbon-carbon double-bond silane coupling agent refers to a silane coupling agent in which the carbon-carbon double bond is directly connected to the Si atom, or the structure containing the carbon-carbon double bond is directly connected to the Si atom but not located on a hydrolyzable group. Specifically, it can be vinyltrimethoxysilane, vinyltriethoxysilane, methacryloxypropyltrimethoxysilane, acryloyloxypropyltrimethoxysilane, methacryloxypropyltriethoxysilane, acryloyloxypropyltriethoxysilane, etc. Epoxy-containing silane coupling agents refer to structures containing epoxy groups that are directly bonded to Si atoms but not located on hydrolyzable groups. Specifically, these can be glycidyl etheroxypropyltrimethoxysilane, glycidyl etheroxypropyltriethoxysilane, β-(3,4-epoxycyclohexane)ethyltrimethoxysilane, β-(3,4-epoxycyclohexane)ethyltriethoxysilane, etc. Specifically, the molar ratio of carbon-carbon double-bond silane coupling agents to epoxy-containing silane coupling agents can be 1:3, 1:2, 1:1, 2:1, 3:1, etc.
[0029] In a more preferred embodiment of this application, insufficient water refers to a molar amount of water lower than the theoretical molar amount of water required for the complete hydrolysis and condensation of carbon-carbon double-bond silane coupling agents and epoxy-containing silane coupling agents, while sufficient water refers to a molar amount of water exceeding the theoretical molar amount of water required for the complete hydrolysis and condensation of carbon-carbon double-bond silane coupling agents and epoxy-containing silane coupling agents. Taking methyltrimethoxysilane as an example, the theoretical amount of water required for the complete hydrolysis of 1 mol of methyltrimethoxysilane is 1.5 mol. Therefore, insufficient water refers to an amount of water added that is less than 1.5 mol, and sufficient water refers to an amount of water added that is more than 1.5 mol. Let the theoretical molar amount of water required for the complete hydrolysis and condensation of carbon-carbon double-bond silane coupling agents and epoxy-containing silane coupling agents be y mol. Further, insufficient water is 0.3-0.7 y mol, and sufficient water can be 1.3 y-20 y mol.
[0030] In a more preferred embodiment of this application, the average particle size of the nano-aluminum hydroxide is 5-50 nm.
[0031] In a more preferred embodiment of this application, the weight ratio of the carbon-carbon double-bond silane coupling agent and the epoxy-containing silane coupling agent to the weight of nano-aluminum hydroxide is 0.1-0.5:1. For example, the weight ratio of the carbon-carbon double-bond silane coupling agent and the epoxy-containing silane coupling agent to the weight of nano-aluminum hydroxide can be 0.1:1, 0.15:1, 0.2:1, 0.25:1, 0.3:1, 0.35:1, 0.4:1, 0.45:1, 0.5:1, etc.
[0032] In a preferred embodiment of this application, the general formula of aminoPOSS is (SiO2). 1.5 ) n R 1 x R 2 y , where R 1 For -CH2CH2CH2NH2, R 2 The amino POSS is selected from C1-C4 alkyl groups, n = 6, 8, 10 or 12, x + y = n, x = 1-2. For example, n = 8, i.e., cage-type octameric silsesquioxane. The amino POSS can be 3-aminopropylheptamethyl cage-type octameric silsesquioxane, 3-aminopropylheptaisobutyl cage-type octameric silsesquioxane, di(3-aminopropyl)hexamethyl cage-type octameric silsesquioxane, etc. The inventors found that if the amino POSS molecule has a large number of amino groups, such as 3 or more, multiple amino groups in one POSS molecule may not react completely due to steric hindrance and other reasons. The presence of excess amino groups leads to a decrease in the flame retardancy and arc erosion resistance of silicone rubber.
[0033] In a preferred embodiment of this application, the appropriate amount of crosslinking agent is 0.8-3 parts of peroxide vulcanizing agent. There are no particular limitations on the peroxide vulcanizing agent; examples include bis(2,4), bis(2,5), dicumyl peroxide, benzoyl peroxide, di-tert-butyl peroxide, 1,4-bis-tert-butylperoxide diisopropylbenzene, etc.
[0034] In a preferred embodiment of this application, the appropriate amount of crosslinking agent consists of 2-100 parts of hydrogen-containing silicone oil and 0.001-0.1 parts of Pt catalyst. There are no particular limitations on the hydrogen-containing silicone oil; for example, the hydrogen content of the hydrogen-containing silicone oil can be 0.1-1.5 wt%, the viscosity (25°C) can be 100-5000 mPa·s, and the volatile matter can be below 0.5 wt%. The amount of hydrogen-containing silicone oil can be set according to a molar ratio of Si-H to vinyl groups in the silicone rubber composition of 1.2-2:1, as is well known to those skilled in the art. There are no particular limitations on the Pt catalyst; for example, it can be a Speier catalyst or a Karstedt catalyst. Further, the weight of Pt in the Pt catalyst can be 10-100 ppm of the weight of the silicone rubber composition.
[0035] In a preferred embodiment of this application, the raw material component further includes 5-50 parts of hydrophobically treated silica. Hydrophobically treated silica refers to silica that has undergone surface treatment with a hydrophobic agent such as trimethylchlorosilane, or surface treatment with a low-viscosity hydroxyl silicone oil (viscosity around 15 mPa·s at 25°C) or hexamethyldisilazane, etc., simultaneously with the addition of silica. The BET specific surface area of the silica can be 100-300 g / m². 2 .
[0036] This application also proposes a disposable film fuse, prepared from the silicone rubber raw material described in any of the above embodiments. The disposable film fuse of this application features good flame retardancy and arc resistance.
[0037] The technical solution of this application will be described in detail below with reference to the embodiments and comparative examples. Unless otherwise specified, the parts in each preparation example, embodiment and comparative example below are parts by weight.
[0038] Preparation Examples 1-3: Preparation of POSS-modified nano-aluminum hydroxide Preparation Example 1 0.1 mol vinyltrimethoxysilane and 0.3 mol glycidyl ether oxypropyltrimethoxysilane were added to 5 L of anhydrous ethanol. 0.3 mol of water was added first to adjust the pH to 3-3.5, and hydrolysis and condensation were carried out for 2 hours. Water was added a second time to bring the total to 1.2 mol, and hydrolysis continued for 0.5 hours. 200 g of 20 nm nano-aluminum hydroxide was added, and the mixture was ultrasonically dispersed for 5 min. The mixture was stirred and reacted for 3 hours. The solid was collected by centrifugation, washed twice with anhydrous ethanol, and dried overnight in a vacuum oven at 40 °C to obtain silane-modified nano-aluminum hydroxide.
[0039] The above 10 parts of silane-modified nano-aluminum hydroxide were ultrasonically dispersed into 100 parts of butyl acetate, and 1 part of 3-aminopropylheptamethyl cage-type octameric silsesquioxane was added. The mixture was stirred at room temperature for 2 hours, then heated to 60°C and reacted for 1 hour. The solid was collected by centrifugation, washed twice with anhydrous ethanol, and dried overnight in a vacuum oven at 40°C to obtain POSS-modified nano-aluminum hydroxide.
[0040] Preparation Example 2 0.2 mol vinyltrimethoxysilane and 0.2 mol glycidyl etheroxypropyltrimethoxysilane were added to 5 L of anhydrous ethanol. 0.4 mol of water was added first to adjust the pH to 3-3.5, and hydrolysis and condensation were carried out for 2 hours. Water was added a second time to bring the total volume to 2 mol, and hydrolysis continued for 0.5 hours. 380 g of 38 nm nano-aluminum hydroxide was added, and the mixture was ultrasonically dispersed for 5 min. The mixture was stirred and reacted for 3 hours. The solid was collected by centrifugation, washed twice with anhydrous ethanol, and dried overnight in a vacuum oven at 40 °C to obtain silane-modified nano-aluminum hydroxide.
[0041] The above 10 parts of silane-modified nano-aluminum hydroxide were ultrasonically dispersed into 100 parts of acetone, and 2.5 parts of 3-aminopropylheptamethyl cage-type octameric silsesquioxane were added. The mixture was stirred at room temperature for 2 hours, then heated to 60°C and reacted for 1 hour. The solid was collected by centrifugation, washed twice with anhydrous ethanol, and dried overnight in a vacuum oven at 40°C to obtain POSS-modified nano-aluminum hydroxide.
[0042] Preparation Example 3 0.3 mol vinyltrimethoxysilane and 0.1 mol glycidyl ether oxypropyltrimethoxysilane were added to 5 L of anhydrous ethanol. 0.2 mol of water was added first to adjust the pH to 3-3.5, and hydrolysis and condensation were carried out for 2 hours. A second addition of water was made to bring the total to 2.5 mol, and hydrolysis continued for 0.5 hours. 300 g of 10 nm nano-aluminum hydroxide was added, and the mixture was ultrasonically dispersed for 5 min. The mixture was stirred and reacted for 3 hours. The solid was collected by centrifugation, washed twice with anhydrous ethanol, and dried overnight in a vacuum oven at 40 °C to obtain silane-modified nano-aluminum hydroxide.
[0043] The above 10 parts of silane-modified nano-aluminum hydroxide were ultrasonically dispersed into 100 parts of butyl acetate, and 4.5 parts of 3-aminopropylheptamethyl cage-type octameric silsesquioxane were added. The mixture was stirred at room temperature for 2 hours, then heated to 60°C and reacted for 1 hour. The solid was collected by centrifugation, washed twice with anhydrous ethanol, and dried overnight in a vacuum oven at 40°C to obtain POSS-modified nano-aluminum hydroxide.
[0044] Comparative Preparation Example 1 0.2 mol vinyltrimethoxysilane and 0.2 mol glycidyl etheroxypropyltrimethoxysilane were added to 5 L of anhydrous ethanol, 2 mol of water was added, and hydrolysis was carried out for 2 hours. Then, 380 g of nano-aluminum hydroxide with an average particle size of 38 nm was added, and the mixture was ultrasonically dispersed for 5 min. The mixture was stirred and reacted for 3 hours. The solid was collected by centrifugation, washed twice with anhydrous ethanol, and dried overnight in a vacuum oven at 40 °C to obtain silane-modified nano-aluminum hydroxide.
[0045] The above 10 parts of silane-modified nano-aluminum hydroxide were ultrasonically dispersed into 100 parts of acetone, and 2.5 parts of 3-aminopropylheptamethyl cage-type octameric silsesquioxane were added. The mixture was stirred at room temperature for 2 hours, then heated to 60°C and reacted for 1 hour. The solid was collected by centrifugation, washed twice with anhydrous ethanol, and dried overnight in a vacuum oven at 40°C to obtain POSS-modified nano-aluminum hydroxide.
[0046] Comparative Preparation Example 2 0.2 mol vinyltrimethoxysilane and 0.2 mol glycidyl etheroxypropyltrimethoxysilane were added to 5 L of anhydrous ethanol, 0.4 mol water was added, and the pH was adjusted to 3-3.5. Hydrolysis and condensation were carried out for 2 hours. 380 g of nano-aluminum hydroxide with an average particle size of 38 nm was added, and the mixture was ultrasonically dispersed for 5 min. The mixture was stirred and reacted for 3 hours. The solid was collected by centrifugation, washed twice with anhydrous ethanol, and dried overnight in a vacuum oven at 40 °C to obtain silane-modified nano-aluminum hydroxide.
[0047] The above 10 parts of silane-modified nano-aluminum hydroxide were ultrasonically dispersed into 100 parts of acetone, and 2.5 parts of 3-aminopropylheptamethyl cage-type octameric silsesquioxane were added. The mixture was stirred at room temperature for 2 hours, then heated to 60°C and reacted for 1 hour. The solid was collected by centrifugation, washed twice with anhydrous ethanol, and dried overnight in a vacuum oven at 40°C to obtain POSS-modified nano-aluminum hydroxide.
[0048] Comparative preparation example 3 Ten parts of the silane-modified nano-aluminum hydroxide from Preparation Example 2 were ultrasonically dispersed into 100 parts of acetone. 2.5 parts of octa(3-aminopropyl)cage-type octapolysilsesquioxane were added, and the mixture was stirred at room temperature for 2 hours. Then, the temperature was raised to 60°C and reacted for 1 hour. The solid was collected by centrifugation, washed twice with anhydrous ethanol, and dried overnight in a vacuum oven at 40°C to obtain POSS-modified nano-aluminum hydroxide.
[0049] In the following examples and comparative examples, the average molecular weight of the vinyl silicone rubber raw rubber was 400,000, the vinyl content was 0.2 wt%, and the volatile matter was 0.2 wt%.
[0050] Example 1 35 parts of POSS-modified nano-aluminum hydroxide from Preparation Example 1 were added to 100 parts of vinyl silicone rubber raw rubber. The mixture was kneaded evenly in a kneader and then transferred to a three-roll mill. 1.5 parts of bis-2,4-curing agent were added and the mixture was passed through a 2 mm, 1 mm, and 0.5 mm roll gap three times. The mixture was then calendered into a 0.1 mm thick sheet and heated at 120 °C for 10 min to obtain a thin sheet silicone rubber.
[0051] Example 2 The difference between Example 2 and Example 1 is that the amount of POSS-modified nano-aluminum hydroxide prepared in Example 1 was increased from 35 parts to 55 parts. The remaining steps remained unchanged.
[0052] Example 3 The difference between Example 3 and Example 1 is that the amount of POSS-modified nano-aluminum hydroxide prepared in Example 1 was increased from 35 parts to 70 parts. The remaining steps remained unchanged.
[0053] Example 4 The difference between Example 4 and Example 1 is that the amount of POSS-modified nano-aluminum hydroxide prepared in Example 1 was increased from 35 parts to 90 parts. The remaining steps remained unchanged.
[0054] Example 5 Add 60 parts of POSS-modified nano-aluminum hydroxide (Preparation Example 2) and 30 parts of BET with a specific surface area of 250 m² to 100 parts of vinyl silicone rubber raw rubber. 2 / g of hydrophobic silica (trimethylchlorosilane treated) was mixed evenly in a kneader and then transferred to a three-roll mill. Hydrogen-containing silicone oil (H content 0.4wt%, viscosity at 25℃ 1600mPa.s, volatile matter 0.4wt%) and Karstedt catalyst (added at 12ppm based on Pt) were added at a Si-H and vinyl molar ratio of 1.5:1. The mixture was passed through three thin passes with roller gaps of 2mm, 1mm and 0.5mm respectively, and then calendered into a sheet with a thickness of 0.1mm. The sheet was heated at 150℃ for 5min to obtain thin silicone rubber sheet.
[0055] Example 6 The difference between Example 6 and Example 5 is that the POSS-modified nano-aluminum hydroxide of Preparation Example 2 in Example 5 was replaced with an equal weight proportion of the POSS-modified nano-aluminum hydroxide of Preparation Example 1. The remaining steps remained unchanged.
[0056] Example 7 The difference between Example 7 and Example 5 is that the POSS-modified nano-aluminum hydroxide from Preparation Example 2 in Example 5 was replaced with an equal weight proportion of the POSS-modified nano-aluminum hydroxide from Preparation Example 3. All other steps remained unchanged.
[0057] Example 8 The difference between Example 8 and Example 5 is that the POSS-modified nano-aluminum hydroxide in Example 2 was increased from 60 parts to 80 parts. The remaining steps remained unchanged.
[0058] Comparative Example 1 The difference between Comparative Example 1 and Example 5 is that the POSS-modified nano-aluminum hydroxide in Preparation Example 2 of Example 5 was replaced with an equal weight proportion of the POSS-modified nano-aluminum hydroxide in Comparative Preparation Example 1. The remaining steps remained unchanged.
[0059] Comparative Example 2 The difference between Comparative Example 2 and Example 5 is that the POSS-modified nano-aluminum hydroxide in Preparation Example 2 of Example 5 was replaced with an equal weight proportion of the POSS-modified nano-aluminum hydroxide in Comparative Example 2. All other steps remained unchanged.
[0060] Comparative Example 3 The difference between Comparative Example 3 and Example 5 is that the POSS-modified nano-aluminum hydroxide in Preparation Example 2 of Example 5 was replaced with an equal weight proportion of the POSS-modified nano-aluminum hydroxide from Comparative Preparation Example 3. All other steps remained unchanged. During processing, it was found that after adding the POSS-modified nano-aluminum hydroxide from Comparative Preparation Example 3, the POSS-modified nano-aluminum hydroxide was difficult to disperse and mix with the silicone rubber compound. This is because the use of octa(3-aminopropyl)cage-type octapolysilsesquioxane resulted in a cross-linked solid filler between POSS and nano-aluminum oxide, making it difficult to disperse and mix with the rubber compound during compounding.
[0061] Comparative Example 4 The difference between Comparative Example 4 and Example 5 is that the POSS-modified nano-aluminum hydroxide from Preparation Example 2 in Example 5 was replaced with a combination of 48 parts of silane-modified nano-aluminum hydroxide from Preparation Example 2 and 12 parts of 3-aminopropylheptamethyl cage-type octameric silsesquioxane. The remaining steps remained unchanged. During processing, it was found that the viscosity of the mixture of silane-modified nano-aluminum hydroxide and silicone rubber was very high, resulting in poor processability.
[0062] Comparative Example 5 0.4 mol glycidyl ether oxypropyltrimethoxysilane was added to 5 L of anhydrous ethanol, 2 mol of water was added, and hydrolysis was carried out for 2 hours. Then, 380 g of nano-aluminum hydroxide with an average particle size of 38 nm was added, ultrasonically dispersed for 5 min, and stirred for 3 hours. The solid was collected by centrifugation, washed twice with anhydrous ethanol, and dried overnight in a vacuum oven at 40 °C to obtain epoxy-modified nano-aluminum hydroxide.
[0063] The above 10 parts of epoxy-modified nano-aluminum hydroxide were ultrasonically dispersed into 100 parts of acetone, and 2.5 parts of 3-aminopropylheptamethyl cage-type octameric silsesquioxane were added. The mixture was stirred at room temperature for 2 hours, then heated to 60°C and reacted for 1 hour. The solid was collected by centrifugation, washed twice with anhydrous ethanol, and dried overnight in a vacuum oven at 40°C to obtain POSS-modified nano-aluminum hydroxide.
[0064] The difference between Comparative Example 5 and Example 5 is that the POSS-modified nano-aluminum hydroxide in Preparation Example 2 of Example 5 was replaced with an equal weight amount of the above-mentioned POSS-modified nano-aluminum hydroxide. The remaining steps remained unchanged.
[0065] Comparative Example 6 The difference between Comparative Example 6 and Example 5 is that POSS-modified nano-aluminum hydroxide was not added. The remaining steps remained unchanged.
[0066] Flame retardancy performance testing: The test sample was cut into 127mm×12.7mm pieces, and the flame retardancy rating was tested according to the UL94 flame retardancy rating test method. The self-extinguishing time after the flame was removed was also calculated.
[0067] Arc erosion resistance: Arc erosion resistance tests were conducted using an arc erosion testing device at DC current, 50A current, and 32V voltage. The arc state and surface erosion state of the test sample were observed. Surface erosion state was rated from 1 to 5, with 5 being obvious erosion and black erosion area, 4 being slightly eroded and yellowish-black erosion area, 3 being no burning and obvious yellowing, 2 being no burning and slightly yellowing, and 1 being no burning and very slight yellowing.
[0068] The results are shown in Table 1 below.
[0069] Table 1 As can be seen from the data in Table 1 above, using the silicone material of this application as a thin-film fuse can achieve a UL94-V0 flame retardant rating, and it also has good arc resistance, with the arc always remaining on the surface of the film and not burning.
[0070] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.
Claims
1. A silicone rubber composition, characterized in that, By weight, the raw material components include 100 parts vinyl silicone rubber raw rubber, 20-90 parts POSS modified nano aluminum hydroxide and an appropriate amount of crosslinking agent; The POSS-modified nano-aluminum hydroxide was prepared by reacting nano-aluminum hydroxide co-modified with carbon-carbon double bonds and epoxy groups with amino POSS at a weight ratio of 1:0.05-0.
5. The carbon-carbon double bond and epoxy group co-modified nano-aluminum hydroxide is prepared by the following method: a carbon-carbon double bond silane coupling agent and an epoxy group silane coupling agent are added together to anhydrous ethanol, an insufficient amount of water is added, the pH is adjusted to 3-5 for hydrolysis and condensation, water is added to the sufficient amount, hydrolysis is continued, nano-aluminum hydroxide is added, the reaction is stirred for 1-10 hours, filtered, washed, and dried to obtain the product. The appropriate amount of crosslinking agent is 0.8-3 parts of peroxide vulcanizing agent or the appropriate amount of crosslinking agent is composed of 2-100 parts of hydrogen-containing silicone oil and 0.001-0.1 parts of Pt catalyst; The general formula of the aminoPOSS is (SiO2). 1.5 ) n R 1 x R 2 y , where R 1 For -CH2CH2CH2NH2, R 2 Selected from C1-C4 alkyl groups, n=6, 8, 10 or 12, x+y=n, x=1-2.
2. The silicone rubber composition according to claim 1, characterized in that, The molar ratio of the carbon-carbon double-bond silane coupling agent and the epoxy-containing silane coupling agent is 3:1 to 1:
3.
3. The silicone rubber composition according to claim 1, characterized in that, The term "insufficient water" refers to a water molar amount lower than the theoretical water molar amount required for the complete hydrolysis and condensation of the carbon-carbon double-bond silane coupling agent and the epoxy-containing silane coupling agent. The term "sufficient water" refers to a water molar amount exceeding the theoretical water molar amount required for the complete hydrolysis and condensation of the carbon-carbon double-bond silane coupling agent and the epoxy-containing silane coupling agent.
4. The silicone rubber composition according to claim 1, characterized in that, The average particle size of the nano-aluminum hydroxide is 5-50 nm.
5. The silicone rubber composition according to claim 1, characterized in that, The weight ratio of the carbon-carbon double-bond silane coupling agent and the epoxy-containing silane coupling agent to the weight of the nano-aluminum hydroxide is 0.1-0.5:
1.
6. A disposable thin-film fuse, characterized in that, It is prepared from the silicone rubber composition according to any one of claims 1-5.
Citation Information
Patent Citations
Surface modified aluminium hydroxide fire retardant and its prepn process
CN101089122A
Preparation method of high-flame-retardant surface modified nano aluminum hydroxide
CN102634065A